ANALISIS IMPLEMENTASI PROGRAM KERJA PMII RAYON MANAJEMEN PENIDDIKAN UIN SYARIF HIDAYATULLAH JAKARTA - Farid, M. Ikhsan; Shodiq, M. Fajrus; Hardiyanti, Rica; Putri, Aiska; Lestari, Ambar Sri (Jurnal Manajemen Pendidikan, 2025)
Student organizations play an important role in shaping students' personality, leadership, and managerial skills. One organization that actively carries out this role is the Indonesian Islamic Student Movement (PMII), especially at the rayon level. This study aims to explore and analyze the various factors that caused the work program not to be implemented during the management period of PMII Education Management Rayon at UIN Syarif Hidayatullah Jakarta. Through a qualitative approach with interview methods, direct observation, and document analysis, it was found that out of a total of 38 programs designed, only 10 programs could be implemented as planned. The main obstacles identified include weak internal coordination, conflicts in activity schedules, limited human and financial resources, lack of evaluation and monitoring systems, and conventional archive management. The results of this study confirm the need for improved communication systems, internal leadership training, digitization of documentation, and periodic evaluation as strategic steps to strengthen organizational governance. The findings are expected to serve as a reference in developing a more effective and sustainable student organization management system.